Praktik Jual Beli Tanah di Bawah Tangan Perspektif Hukum Islam dan Undang - Undang Pertanahan - Dina Setiani; Ah Kholishayatuddin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Buying and selling land is the process of transferring ownership of land from the seller to the buyer, which is carried out in an open and cash manner. The transfer of land rights is supervised and regulated by government regulations where a deed of sale and purchase (AJB) must be made by the competent authority as evidence that a legal act of transferring rights has taken place. This research is a type of field research using qualitative research methods. Sources of data obtained from primary data, namely from interviews about the practice of buying and selling land under the hands of the perspective of Islamic law and the Land Law in Trukan Village, Pracimantoro District, Wonogiri. As well as secondary data sources obtained from documentation, reference books, journals, and Basic Agrarian Laws as well as Government Regulations on land registration and Government Regulations concerning Land Deed Maker Officials (PPAT). Based on the results of the study, In the perspective of Islamic law, the status of land ownership in a free sale is perfect property (milk at-tam) while the annual sale is imperfect property (milk naqish), the validity of the sale and purchase of land in terms of the obligations of the seller and buyer, has fulfilled the pillars and conditions of the sale and purchase. This transaction is a legal sale and purchase in Islam. The custom in society that is in accordance with the sale and purchase of private land is 'Urf, which is 'urf fi'li and urf sahih. Meanwhile, from a positive legal perspective in Indonesia, referring to government regulations and land laws, the legitimacy and legal status of buying and selling illegal land is not a legal act and has not yet had a strong and permanent legal force. Abstrak Jual beli tanah merupakan proses pemindahan hak milik atas tanah dari penjual kepada pembeli yang dilakukan secara terang dan tunai. Peralihan hak atas tanah diawasi dan diatur dengan peraturan pemerintah yangmana harus dibuat akta jual beli (AJB) oleh pihak yang berwenang sebagai bukti telah terjadi perbuatan hukum pemindahan hak. Penelitian ini merupakan jenis penelitian lapangan (field research) dengan menggunakan metode penelitian kualitatif. Sumber data diperoleh dari data primer yaitu dari hasil wawancara tentang praktik jual beli tanah di bawah tangan perspektif hukum Islam dan Undang-Undang Pertanahan di Desa Trukan, Kecamatan Pracimantoro, Wonogiri. Serta sumber data sekunder yang diperoleh dari dokumentasi, buku-buku referensi, jurnal, dan Undang-Undang Pokok Agraria serta Peraturan Pemerintah tentang pendaftaran tanah dan Peraturan Pemerintah tentang Pejabat Pembuat Akta Tanah (PPAT). Berdasarkan hasil penelitian, dalam perspektif hukum Islam, status kepemilikan tanah pada jual lepas merupakan milik sempurna (milk at-tam) sedangkan jual tahunan merupakan milik tidak sempruna (milk naqish), keabsahan jual beli tanah ditinjau dari kewajiban penjual dan pembeli, telah memenuhi rukun dan syarat jual beli, transaksi ini merupakan jual beli yang sah dalam Islam. Kebiasaan dalam masyarakat yang sesuai dengan jual beli tanah di bawah tangan ini merupakan 'Urf, yaitu merupakan ‘urf fi’li dan ‘urf sahih. Sedangkan dalam pandangan hukum positif di Indonesia mengacu pada peraturan pemerintah dan undang-undang pertanahan, keabsahan dan status hukum jual beli tanah di bawah tangan ini bukan merupakan perbuatan hukum yang sah dan belum berkekuatan hukum yang kuat dan tetap.